MEMBANGUN KINERJA SUPPLY CHAIN UMKM MELALUI KEPERCAYAAN, KUALITAS INFORMASI, DAN BERBAGI INFORMASI: ENHANCING MSME SUPPLY CHAIN PERFORMANCE THROUGH TRUST, INFORMATION QUALITY, AND INFORMATION SHARING - Nawara, Shadiqin; Basri, Yesi Mutia; Silfi, Alfiati (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2025)
Only 18% of MSMEs in Indonesia implement good supply chain management. This is reflected in issues such as difficulty obtaining affordable, high-quality and timely raw materials.This research was conducted with the aim of analyzing the influence of trust and information quality on the performance of supply chain management by sharing information as a mediating variable. The amount of data used was 127 and processed using SmartPLS 4 software. The results of this study show that the trust and quality of information affect the performance of supply chain management. In addiction, information sharing is able to mediate the influence of trust and information quality on supply chain management performance. The mediation test that occured in this study was partial mediation. Problems such as shortages of raw materials, high cost of raw materials and delays in the delivery of raw materials can be overcome by building strong trust with business partners, improving the quality of information received and encouraging avtive and open information sharing practices. Consistently and sustainably it will create a more responsive, effective and efficient supply chain.